The development of magmatism along the Cameroon Volcanic Line: Evidence from seismicity and seismic anisotropy. Issue 5 (8th May 2014) - De Plaen, R. S. M.; Bastow, I. D.; Chambers, E. L.; Keir, D.; Gallacher, R. J.; Keane, J.
Abstract The Cameroon Volcanic Line (CVL) straddles the continent‐ocean boundary in West Africa but exhibits no clear age progression. This renders it difficult to explain by traditional plume/plate motion hypotheses; thus, there remains no consensus on the processes responsible for its development. To understand better the nature of asthenospheric flow beneath the CVL, and the effects of hotspot tectonism on the overlying lithosphere, we analyze mantle seismic anisotropy and seismicity. Cameroon is relatively aseismic compared to hotspots elsewhere, with little evidence for magmatism‐related crustal deformation away from Mount Cameroon, which last erupted in 2000. Low crustal Vp/Vs ratios (∼1.74) and a lack of evidence for seismically anisotropic aligned melt within the lithosphere both point toward a poorly developed magmatic plumbing system beneath the CVL. Null SKS splitting observations dominate the western continental portion of the CVL; elsewhere, anisotropic fast polarization directions parallel the strike of the Precambrian Central African Shear Zone (CASZ). The nulls may imply that the convecting upper mantle beneath the CVL is isotropic, or characterized by a vertically oriented olivine lattice preferred orientation fabric, perhaps due to a mantle plume or the upward limb of a small‐scale convection cell. Precambrian CASZ fossil lithospheric fabrics along the CVL may have been thermomechanically eroded during Gondwana breakup ∼130 Ma, with an isotropic lower lithosphere subsequently reforming due to cooling of the slow‐moving African plate. Small‐scale lithospheric delamination during the 30 Ma recent development of the line may also have contributed to the erosion of the CASZ lithospheric fossil anisotropy, at the same time as generating the low‐volume alkaline basaltic volcanism along the CVL.